Aksiologi dalam Perspektif Islam - Zainuddin, M. (UIN Maulana Malik Ibrahim Malang, 2002)
Islam is the religion of Allah which contains the teachings and guidance that must be held and used as a guidance by its adherents to the happiness of the world and in the afterlife. The teachings of Islam include the teachings of monotheism and shari'a or faith and charity. Of course these aspects of Islamic teachings must be understood well through learning or seeking knowledge. This is where science is necessary and important. Thus science is part of the religion itself. It occupies a position or as part of religion and has a function as an instrument or means to obtain the goal of religion, which is to obtain the happiness of the world and the hereafter. In other words, the relationship between religion and science is symbiotic, because religion calls on the pursuit of science and gives a noble position to the scientist. Similarly, the relationship occurs between religion and philosophy. Both have the same direction. Philosophy is the knowledge of what is right. The religion explains what is right and good based on revelation and reason. Islam adalah agama Allah SWT yang berisikan ajaran-ajaran dan tuntunan yang harus dipegang dan dijadikan pedoman oleh pemeluknya untuk kebahagiaan dunia maupun di akhirat. Ajaran-ajaran Islam tersebut meliputi ajaran tauhid dan syari’ah atau iman dan amal. Sudah barang tentu aspek-aspek ajaran Islam tersebut harus dipahami dan dimengerti melalui belajar atau mencari ilmu. Di sinilah ilmu itu perlu dan penting. Dengan demikian ilmu merupakan bagian dari agama itu sendiri. Ia menempat posisi atau kedudukan sebagai bagian dari agama dan memiliki fungsi sebagai instrumen/sarana untuk memperoleh tujuan agama, yaitu memperoleh kebahagiaan dunia maupun akhirat. Dengan kata lain, hubungan agama dan ilmu bersifat simbiotik, karena agama menyeru pada pencarian ilmu dan memberikan posisi mulia bagi ilmuwan. Demikian pula hubungan antara agama dan filsafat. Keduanya memiliki arah yang sama. Filsafat adalah pengetahuan tentang apa yang benar. Adapun agama menerangkan apa yang benar dan baik berdasarkan wahyu dan akal.